Pengaruh Inovasi Produk dan Brand Awereness terhadap Keputusan Pembelian pada Usaha Multinasional (Study Kasus PT. Sepatu Bata Tbk) - Andari, Ni Luh Indah; Usadha, I Dewa Nyoman; Suparta, I Nyoman (Lembaga Yasin AlSys, 2023)
This research was conducted at PT Shoe Bata Tbk, Denpasar branch, namely Bata Cokro 87 Denpasar. The aim of this research is to find out whether product innovation and brand awareness partially and simultaneously influence purchasing decisions in multinational businesses using the case study of PT Shoe Bata Tbk, Denpasar branch. This research used 45 samples using the quota sampling method. Data analysis in this research is qualitative using the multiple linear regression method. research shows that (1) Product Innovation has a positive and significant effect on purchasing decisions as evidenced by the calculated t value > t table (3.524 > 2.018); 2) Brand Awareness has a positive and significant effect on purchasing decisions, as evidenced by the calculated t value > t table (6.049 > 2.018) 3) Product Innovation and Brand Awareness simultaneously influence purchasing decisions, as evidenced by the calculated F value of 46.913 >???? table 3,2199. The determinant coefficient obtained was 0.691 or 691%.